English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Can you please show me the steps in solving this problem. Work one side of the equation.

1 + cosx................sinx
________ = _________

sinx....................1 - cosx


(pretend the dots are not there, I did that to allign the numbers under the division sign)
.
.
.

2007-03-10 11:00:48 · 4 answers · asked by Shawn 1 in Science & Mathematics Mathematics

4 answers

Prove the identity (1 + cosx)/sinx = sinx/(1 - cosx)

Let's work with the Right Hand Side.

Right Hand Side = sinx/(1 - cosx)
= sinx(1 + cosx) / [(1 - cosx)(1 + cosx)]
= sinx(1 + cosx) / (1 - cos²x)
= sinx(1 + cosx) / sin²x
= (1 + cosx) / sinx = Left Hand Side

2007-03-10 11:05:58 · answer #1 · answered by Northstar 7 · 0 0

recall the identity (sin(x))^2 + (cos(x))^2 =1. that is what you are looking here.
as with any rational problem it can be solve by multiplying each side by the denominators. the result will be
(1-cosx)(1+cosx)=(sinx)^2
when you finsih multiplying the left side and solving the equation 1=the identity

2007-03-10 19:28:27 · answer #2 · answered by molawby 3 · 0 0

(1 + cosx)/sinx = (1 + cosx)(1 - cosx)/sinx(1 -cosx) ie multiply top and bottom by (1 -cosx)

The denominator is (1 +cosx)(1 -cosx) = (1 - cos^2x) = sin^2x

Thus (1 + cosx)/sinx = (1 + cosx)(1 - cosx)/sinx(1 -cosx) = sin^2x/sinx(1 - cosx) = sinx/(1 -cosx) which is the RHS qed

2007-03-10 19:30:52 · answer #3 · answered by physicist 4 · 0 0

Alright. Take the first equation and multiply the top and bottom by 1 - cos(x).

On the top you get 1 - cos(x)^2
And on the bottom you get sin(x) - sin(x)*cos(x)

You use a trig identity to get 1 - cos(x)^2=sin(x)^2
Then, cancel the sin(x)'s on the top and bottom.

You get sin(x)/(1 - cos(x))

2007-03-10 19:22:46 · answer #4 · answered by Collin 2 · 0 0

fedest.com, questions and answers